PERBEDAAN HASIL BELAJAR IPS EKONOMI MENGUNAKAN METODE GIVING QUESTION AND GETTING ANSWER DENGAN METODE LEARNING STARTS WITH A QUESTION SISWA KELAS X SMK N 1 SUTERA PESISIR SELATAN - Deprisal, Deprisal; Tanjung, Mirna; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This research was motivated by the low economic learning outcomes of students of class X of SMK N 1 Silk Academic Year 2013/2014. This is because the less active students in the learning process. This study aims to determine the differences in learning outcomes IPS Economic giving students the application of the method question and getting answer with stars learning method with a question in class X SMK N 1 Silk.This research is an experimental study. The study population is a class X student of SMK N 1 Silk academic year 2013/2014. Samples were taken by purposive sampling technique, was chosen as the experimental class Xak3 class 1 and class 2 XAk1 as an experimental class. Instrument used is a form of achievement test. Data analysis techniques to test the hypothesis is to test Z.Based on the analysis of data obtained by the average value of the experimental class 1 79.90 and an average class experiment 2 is 71.71. The results of the analysis of the data found 2,576 Zhitung value greater than 1.960 Ztabel price which means the hypothesis is accepted at significance level Î± = 0.05. It can be concluded that the results of social studies students with the application of the method Economics question and getting the answer giving is better than IPS Economics student learning outcomes that uses learning methods starst with a question in class X SMK N 1 Silk.